Analisis SWOT dalam Strategi Pemasaran Produk Pembiayaan di KSPP. Syariah BMT NU Jawa Timur Cabang Utama Sumenep - Nafisah Nafisah; Laurentia Maria Husada (Universitas 45 Surabaya, 2024)
The problems faced by Islamic financial institutions are marketing islamic financing products, regulatory challenges, the risk of non-performing financing, and the lack of awareness and understanding of islamic financing products among the public. This research aims to develop an effective marketing strategy for Islamic financing products using SWOT analysis. Qualitative research method using case study, sampling method using purposive sampling. The sample consists of three respondents who are experts in the field of Islamic financing and marketing including the head of the KSPP branch. Sharia BMT NU East Java Main Branch Sumenep. Data collection using primary data through in-depth interviews, observation, and documentation. Analysis using the SWOT matrix analysis framework. From the results of the SWOT matrix, it can be seen that the strength and opportunity factors are more than the weakness and threat factors. The conclusions of this study are: (1) To market financing products, KSPP. Syariah BMT NU East Java Main Branch Sumenep uses a door to door strategy, builds networks, word of mouth, and provides excellent service and provides satisfying facilities to increase customer trust and satisfaction so that customers remain loyal; (2) The results of the SWOT analysis explain that KSPP. Syariah BMT NU East Java Main Branch Sumenep has the ability to compete in a competitive market by taking advantage of opportunities and continuing to improve its strengths.